The Mantle Odes - Francis Robinson (International Institute of Islamic Thought, 2011)
Non-Muslims, perhaps blinded by the claims of their own faiths, have long underestimated Muslim reverence for the Prophet Muhammad. By the same token, they have paid relatively little attention to Muslim traditions of praising the Prophet, whether it be the naths sung by Sufi qawwali musicians in South Asia, the maulid lectures on the first twelve days of Rabi al- Awwal ‒ or the biographies of the Prophet, which have become so numerous over the past century. This is unfortunate because, intermingled with praise for the Prophet, there are often other messages, which non-Muslims need to note if they are better to understand their Muslim neighbors. The Mantle Odes contains translations, and interpretations in their context, of three of the most highly prized poems in the Arab-Islamic tradition in praise of the Prophet. One poem dates from the time of the Prophet, the second from the thirteenth century AC under the Mamluks, and the third from Egypt under colonial rule in the early twentieth century. The author’s aim is “to bring these Islamic devotional masterpieces into the purview of contemporary literary interpretation in a way that makes them culturally relevant and poetically effective for the modern reader, whether Muslim or non-Muslim” (xi) ...